2017
DOI: 10.1016/j.acra.2017.03.021
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fatigue on Satisfaction of Search in Chest Radiography

Abstract: Purpose To assess the nature of the satisfaction of search (SOS) effect in chest radiography when observers are fatigued; determine if we could replicate recent findings that have documented the nature of the SOS effect to be due to a threshold shift rather than a change in diagnostic accuracy as in earlier film-based studies. Materials and Methods Nearing or at the end of a clinical workday, 20 radiologists read 64 chest images twice, once with and once without the addition of a simulated pulmonary nodule. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…5,6 The first study investigating the effects of fatigue on interpretation involving multiple abnormalities was recently published. 7 This study, however, was limited to plain film chest radiography thus the results may not generalize to more advanced imaging techniques, such as CT. In fact, earlier studies [that did not include satisfaction of search (SOS)] demonstrated that the impact of fatigue may indeed differ for plain film and chest CT so there is a reason to believe that the same may hold true with SOS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 The first study investigating the effects of fatigue on interpretation involving multiple abnormalities was recently published. 7 This study, however, was limited to plain film chest radiography thus the results may not generalize to more advanced imaging techniques, such as CT. In fact, earlier studies [that did not include satisfaction of search (SOS)] demonstrated that the impact of fatigue may indeed differ for plain film and chest CT so there is a reason to believe that the same may hold true with SOS.…”
Section: Introductionmentioning
confidence: 99%
“…2 The effects of an extended workday have been investigated in laboratory studies using a number of tasks that simulate clinical interpretation. [5][6][7] Studies using single lesion detection tasks [fractures in bone images and nodules in computed radiography (CR) and computed tomography (CT) chest] generally demonstrated a statistically significant average decrease in diagnostic accuracy of ∼4%. 5,6 The first study investigating the effects of fatigue on interpretation involving multiple abnormalities was recently published.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Необходимо иметь в виду, что сбор анамнеза у таких пациентов не всегда возможен и показатели клинического обследования в 20-50 % случаев с тупыми травмами бывают недостоверными [3,4]. Было высказано предположение о том, что после нахождения первой травмы той или иной анатомической области врач довольствуется полученным результатом поиска и прекращает искать иные потенциальные повреждения в других анатомических областях, в связи с чем феномен получил название «насыщения поиска» [5]. При наличии травмы головы c нарушением сознания достоверность обследования при выявлении травмы живота падает до 16 % [6,7].…”
Section: Introductionunclassified
“…Although a radiology work environment is categorized as shift work, disturbances in daily sleeping cycles are associated with physiological and behavioral effects as well as a loss of the rhythm entrainment [2]. Considerable fatigue and human error affect radiology practices with recent literature covering how diagnostic accuracy is compromised after long working hours [4] [5] [6][3] [7]. Under financial pressure, radiologists' practices are adopting a faster and more agile productivity style to accommodate larger workloads.…”
Section: Introductionmentioning
confidence: 99%